Upaya Peningkatan Hasil Belajar Senam Irama Menggunakan Metode Pembelajaran Problem Based Learning (PBL) Siswa Kelas VIII SMP Labschool UNESA 3 - Syahrial Zaky Pranoto; Nanik Indahwati; Sigra Santika Satria Dhani (Journal of Creative Student Research, 2024)
This research aims to determine efforts to improve rhythmic gymnastics learning outcomes using the problem based learning (PBL) method for class VIII SMP Labschool UNESA 3 students. This research is classroom action research which uses class VIII C as the sample. This research was carried out in two cycles, with the stages of each cycle being planning, implementation, observation and reflection. The data collection technique uses final grades and observation of classroom situations during the learning process. The research results obtained were that in cycle I the number of students who completed the KKM was 15 students with an observation achievement of 70%. And in cycle II there was an increase in the number of students completing their final grades to 21 students with the completeness of the observation results reaching 89%. Based on these results, it is concluded that in implementing the problem based learning method, the final grades or student learning outcomes increase.